Learner perceptions of a national CLIL innovation in foreign languages in the Republic of Ireland (5474) - Bower, Kim; Rutgers, Dieuwerke; Quigley, Laura (Frontiers in Education, 2024)
This paper describes a Content and Language Integrated Learning (CLIL) curriculum innovation to improve motivation in language learning undertaken in the Republic of Ireland through a national pilot in Transition Year (TY) in 2021-2023 for learners aged 15-16. Here we extract data from part of an empirical evaluation study focussing on the research question, what are learner perceptions of learning through CLIL approaches in a national pilot module? A CLIL module on the theme of Fair Trade based on geographical and mathematical skills and content was taught through either French, German, Italian or Spanish. Models varied between schoolsmost undertook the module by teaching two to three lessons per week within a six-eight week period. A minority taught through this approach throughout the year. Results are presented from learner focus groups in three diverse school contexts and an online learner questionnaire drawn from all participating learners in these schools. Group discussions were recorded and transcribed. Thematic analysis was undertaken based on the Process Motivation Model for investigating CLIL in the classroom (PMM). Analysis and discussion include the positive impact on a large majority of learners and practical implications around the nature of learning a linear school subject in TY. Lessons learned include the need to extend this innovation to the wider curriculum, and the need for further professional learning for teachers. Constraints due to the nature of TY year and the module are acknowledged.